2018
DOI: 10.1093/mnras/sty1417
|View full text |Cite
|
Sign up to set email alerts
|

Nucleosynthesis in Primordial Hypernovae

Abstract: We investigate the relationship between explosion energy and nucleosynthesis in Population III supernovae and provide nucleosynthetic results for the explosions of stars with progenitor masses of 15 M , 20 M , 30 M , 40 M , 60 M , and 80 M , and explosion energies between approximately 10 50 erg and 10 53 erg. We find that the typical abundance pattern observed in metal-poor stars are best matched by supernovae with progenitor mass in the range 15 M -30 M , and explosion energy of ∼ (5 − 10) × 10 51 erg. In th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 109 publications
1
35
0
Order By: Relevance
“…Overall, the explosion of the massive Pop III star progenitor of HE 1327−2326 is thus more energetic than previously thought (i.e., a hypernova), in line with more recent studies, such as Grimmett et al (2018). Interestingly, previous work has suggested that only faint mixing and fallback first SNe would seed carbon-enhanced metal-poor (CEMP) stars such as HE 1327−2326, since their host minihalos would be disrupted by any larger energy input (Cooke & Madau 2014).…”
Section: Comparison To Aspherical Sne Modelssupporting
confidence: 86%
See 2 more Smart Citations
“…Overall, the explosion of the massive Pop III star progenitor of HE 1327−2326 is thus more energetic than previously thought (i.e., a hypernova), in line with more recent studies, such as Grimmett et al (2018). Interestingly, previous work has suggested that only faint mixing and fallback first SNe would seed carbon-enhanced metal-poor (CEMP) stars such as HE 1327−2326, since their host minihalos would be disrupted by any larger energy input (Cooke & Madau 2014).…”
Section: Comparison To Aspherical Sne Modelssupporting
confidence: 86%
“…Our best fit model has an initial mass cut of M cut =1.64 M , outer boundary mixing region mass of M mix = 5.65 M and an ejection factor of f = 0.0002. To increase specifically the zinc yield of a mixing and fallback SNe model, the explosion mechanism was modified such that the matter density is artificially reduced, to mimic a high entropy explosion environment, which is required for increased explosive nucleosynthesis (Maeda & Nomoto 2003;Tominaga et al 2007a,b;Grimmett et al 2018). In this modified framework, elements formed in the deepest layers during the explosion, such as zinc, are (at least partially) mixed upward and then ejected.…”
Section: Comparison To Aspherical Sne Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, it has become common practice to use SN models to infer the properties of the primordial progenitors of the most metal-poor observed stars, both for individual stars (e.g., Heger & Woosley 2010;Hansen et al 2011;Nomoto et al 2013;Ishigaki et al 2014;Bessell et al 2015;Placco et al 2016) and for large samples (Cayrel et al 2004;Fraser et al 2017;Ishigaki et al 2018). Additionally, constraints on the primordial IMF can be inferred from bulk properties of metal-poor stars with semi-analytical models (de Bennassuti et al 2017;Hartwig et al 2018;Tarumi et al 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…VMP DLAs have allowed for an empirically driven approach to quantify the abundances of metals ejected from the first stars. They are complementary to using VMP stars for the same purpose (e.g., Grimmett et al 2018;Ishigaki et al 2018;Griffith et al 2021a, K19). Improvements that would benefit future work us-ing VMP DLAs include increasing the number of elemental abundances measured from VMP DLA spectra so that more abundance ratios can be constrained, and increasing the sample size of VMP DLAs to improve the statistics of the empirical constraints.…”
Section: Discussionmentioning
confidence: 99%